METAPHORICAL TERMINOLOGY IN ANCIENT TEXTS OF TRADITIONAL CHINESE MEDICINE: PROBLEMS OF UNDERSTANDING AND TRANSLATION - Qiuhua Sun; Irina S. Karabulatova; Jinna Zou; Chen Kuo (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The author’s hypothesis proceeds from the position that the ancient treatises of traditional Chinese medicine (TCM) describe metaphorically an ethnocultural understanding of neuro-linguistic and psychophysiological processes in the human body from the perspective of communication between large and small. TCM terms are medical concepts that also contain deep philosophical and linguistic-cultural content plans, due to the Wenyan-style in which TCM treatises are written. The purpose of the work is to identify the patterns of the language of these ancient texts in the context of the interpretation presented in them through the hierarchy of ‘state and subjects’. The use of methodological holism made it possible to develop a new approach to the texts of traditional Chinese medicine from the standpoint of communication studies and neuropsycholinguistics. The mythologized interpretation of the concepts in the ancient treatises of TCM is associated with the signification of any health problem in the form of an expanded metaphor characterizing the problem as a violation of ‘communication’ in the body-‘state’ between ‘vassals’, ‘individual social groups’ and their ‘leaders’. This positioning of the body’s work through the prism of social relations provides an understanding of the interpretation of relationships in ancient Chinese society as a whole.